Putting Behavior Into Context: Exploring the Contours of Social Capital Influences on Environmental Behavior. (April 2017) - Cho, Sungchul; Kang, Hyeongsik
Although well-theorized causal explanations exist at the person level, scholars of environmental behavior have long neglected the social nature of environmental activism. Using a unique data set of individuals nested within local communities along the Han River, South Korea, we propose a novel empirical model for analyzing the contextual effect of social capital on different sets of self-reported environmental behaviors. Our findings, based on multilevel structural equation modeling, indicate that the community-level construct of social capital is a significant predictor of spatial variations in both private and public environmental behaviors, whereas the person-level construct of community ties has predictive power for private environmental behavior. Understanding these multilayered paths in which social capital relates to pro-environmental behaviors provides a crucial balance to previous single-level findings.